Offsetting Receivables Against Zakat Obligations: A Study of Imam al-Layth ibn Saʿd's Jurisprudential Reasoning - Ahmad Budiman; Busyro Busyro; Edi Rosman; Nofiardi Nofiardi (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study aims to examine Imam al-Layth ibn Saʿd’s legal opinion on the permissibility of treating receivables as zakat and to analyze the jurisprudential foundations underlying his position. The research employs a qualitative library-based method using fiqh and uṣūl al-fiqh approaches through a systematic analysis of classical legal texts, authoritative works documenting al-Layth’s opinions, and contemporary literature on zakat and debt. The findings reveal that Imam al-Layth permits a creditor to discharge zakat obligations by cancelling receivables owed by poor or insolvent debtors, considering such debt forgiveness to effectively realize the objectives of zakat by alleviating the financial burden of eligible beneficiaries. His legal reasoning is primarily based on the principles of maṣlaḥah (public benefit) and the substantive equivalence between debt cancellation and direct zakat distribution, rather than a strict interpretation of tamlīk (transfer of ownership). The study concludes that al-Layth’s opinion represents a purposive approach to Islamic jurisprudence that emphasizes the realization of social justice and the objectives of zakat over formal legal procedures. This research contributes to Islamic legal scholarship by providing a comprehensive analysis of an alternative classical juristic opinion and offering a maqāṣid-based framework for contemporary discussions on zakat administration, debt relief, and Islamic social finance.